2017
DOI: 10.1002/ece3.3457
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the population structure of hardhead silverside,Atherinomorus stipes(Teleostei: Atherinidae), in Belize and the Florida Keys usingnd2

Abstract: Little is known about the natural history, biology, and population genetic structure of the Hardhead Silverside, Atherinomorus stipes, a small schooling fish found around islands throughout the Caribbean. Our field observations of A. stipes in the cays of Belize and the Florida Keys found that populations tend to be in close association with the shoreline in mangrove habitats. Due to this potential island‐based population structuring, A. stipes represents an ideal system to examine questions about gene flow an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…If the haplotype network (Figure 3) is rooted at Haplotype 1 as per Tipton, Gignoux-Wolfsohn, Stonebraker and Chernoff [20], then there are at least three distinct lineages; the divergence of nuclear microsatellite alleles is well described above and the populations are distinct from their nearest neighbors in the Coginchaug River (Table 3, Figure 4 lower). As more species are examined at microgeographic scales, such as that by Nash, Kraczkowski and Chernoff [8], we predict that divergence and structuring patterns of the type demonstrated herein will become the norm rather than the exception. If we recognize evolutionary potential as suggested by Tim, Anne, Boyd, Micah, Douglas, Aaron and Bonnie [56], then populations meeting the other criteria of Moritz [54] will be recognized as ESU's-a situation we would agree with but may be impractical.…”
Section: The Results Of Amovas and Bayesian A Posteriori Classifications Of Allynmentioning
confidence: 78%
See 1 more Smart Citation
“…If the haplotype network (Figure 3) is rooted at Haplotype 1 as per Tipton, Gignoux-Wolfsohn, Stonebraker and Chernoff [20], then there are at least three distinct lineages; the divergence of nuclear microsatellite alleles is well described above and the populations are distinct from their nearest neighbors in the Coginchaug River (Table 3, Figure 4 lower). As more species are examined at microgeographic scales, such as that by Nash, Kraczkowski and Chernoff [8], we predict that divergence and structuring patterns of the type demonstrated herein will become the norm rather than the exception. If we recognize evolutionary potential as suggested by Tim, Anne, Boyd, Micah, Douglas, Aaron and Bonnie [56], then populations meeting the other criteria of Moritz [54] will be recognized as ESU's-a situation we would agree with but may be impractical.…”
Section: The Results Of Amovas and Bayesian A Posteriori Classifications Of Allynmentioning
confidence: 78%
“…The degree of connectivity among habitats within a watershed is a critical driver of the genetic population structure of freshwater fishes, because barriers to movement limit gene flow and may lead to loss of genetic diversity or even the production of novel genetic signatures [3] [4] [5]. The degree of divergence among populations should increase relative to the number and relative strengths of barriers, and/or the geographic distance that isolates populations [3] [6] [7] [8]. Isolation by distance is expected in riverine fishes but is not always found [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, there are species that have one food guild, and one type of prey, better adapted to a specialist strategy, such as the juveniles of A. stipes, with a diet based on the consumption of zoeas larvae, of decapods and copepods (Vaslet et al, 2015). Atherinomorus stipes is related with mangrove areas in the Mexican-Caribbean; notwithstanding, its presence is limited by ecosystem alterations, more so, if there is an increase in turbidity of the water, limiting foraging and hindering its encounter with preferred prey (Nash et al, 2017). This high turbidity in water observed for the restored zone probably explains the low abundance of this specie.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their large populations and ecological importance, very little is known about A. stipes population dynamics. Other Atherinidae species have demersal eggs that attach to nearby substrate using chorionic filaments, and it is likely that A. stipes also have demersal eggs, limiting embryonic dispersal ( Takemura et al 2004 ; Nash et al 2017 ). It may be expected that little genetic structure exists among A. stipes populations due to their ubiquity, yet egg attachment to local substrate may limit early life stage dispersal and could drive population differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…It may be expected that little genetic structure exists among A. stipes populations due to their ubiquity, yet egg attachment to local substrate may limit early life stage dispersal and could drive population differentiation. Previously, a study using a single mitochondrial locus ( nd2 ) found high haplotype divergence but no evidence of isolation by distance (IBD) among Belize cays and Florida Keys populations ( Nash et al 2017 ). However, because these conclusions are drawn from a single mitochondrial locus, they may not reflect nuclear genetic diversity patterns.…”
Section: Introductionmentioning
confidence: 99%